Adaptive Error Control Schemes For Supporting Quality Of Service In Wireless Atm Networks - Khatun, Sabira (2003)
This thesis deals with the error control problems, which is one of the major issues for supporting quality of service (QoS) in wireless ATM (W A TM). Generally in wireless communication, error is induced by impairment prone wireless links. As a method of quality of service based error control, the design and performance evaluation of a retransmission based error control scheme is proposed to overcome wireless channel impairments for multimedia traffic support over wireless A TM networks. The purpose of the proposed error control scheme is to provide error-free services to the higher layers by either correcting the errors in a packet or recovering corrupted packets by retransmission in a wireless link. From the perspective of error control, multimedia traffic can be divided into two types: loss-sensitive traffic and delay-sensitive traffic. To support all these traffic over W ATM networks, we propose two approaches for error control. One approach is to utilize the reliable AAL protocol, which are referd to as AALXl and AALX2, as the end-to-end error control, based on our knowledge-based selectivereject automatic repeat request (KSRARQ) scheme, and adaptive header protection with KSRARQ scheme for loss-sensitive and delay-sensitive traffic, respectively.